Risk factors associated with high infant and child mortality in Lesotho - Mokoena, Mathabang P (Centre for Actuarial Research (CARE), 2015)
This study uses the 2004 and 2009 Lesotho Demographic and Health Surveys (LDHS) to: 1) identify the risk factors that affect mortality at neonatal, post-neonatal, and child ages, and, specifically, to determine the effect of mother’s HIV status on child mortality; 2) investigate how the risk factors that affect mortality have changed between the two periods, 2000-2004 to 2005-2009; and 3) determine if the risk factors are age dependent, that is, whether the effects of risk factors vary for different child ages.